2012
DOI: 10.2131/jts.37.1045
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of reactive oxygen species by the vacuolar-type (H<sup>+</sup>)-ATPase inhibitors bafilomycin A1 and concanamycin A in RAW 264 cells

Abstract: -Treatment of the mouse leukemic cell line RAW 264 with bafilomycin A1 or concanamycin A, inhibitors of vacuolar-type (H + )-ATPases (V-ATPases), significantly increased the production of reactive oxygen species (ROS) and decreased cell viability. These effects were significantly suppressed by the presence of N-acetyl cysteine (NAC), an ROS scavenger. si-RNA mediated knockdown of the gene for the c subunit of the V0 domain of V-ATPase also resulted in an increase in ROS production and a decrease in cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…In agreement with increased ROS formation in murine macrophages exposed to the V-ATPase inhibitors bafilomycin A1 or to concanamycin A [31], archazolid enhanced LPS-induced ROS formation in human macrophages, which was sensitive to the NDAPH oxidase inhibitor DPI. Of interest, DPI also blocked archazolid-induced TNFα release implying a requirement of ROS in this respect.…”
Section: Our Detailed Analysis Of Pks and Transcription Factors That supporting
confidence: 62%
See 4 more Smart Citations
“…In agreement with increased ROS formation in murine macrophages exposed to the V-ATPase inhibitors bafilomycin A1 or to concanamycin A [31], archazolid enhanced LPS-induced ROS formation in human macrophages, which was sensitive to the NDAPH oxidase inhibitor DPI. Of interest, DPI also blocked archazolid-induced TNFα release implying a requirement of ROS in this respect.…”
Section: Our Detailed Analysis Of Pks and Transcription Factors That supporting
confidence: 62%
“…Previous studies showed that macrophages from different origins and species express V-ATPase and respond to VATPase inhibitors in different ways [13,31,[34][35][36][37][38][39]. We first confirmed V-ATPase expression in human monocyte-derived macrophages [40] by Western blot (not shown) and by using immunofluorescence microscopy where no obvious differences regarding V-ATPase subcellular localization between the macrophage phenotypes were immediately apparent (Fig.…”
Section: Expression Of V-atpase In Macrophages and Effects Of The V-asupporting
confidence: 59%
See 3 more Smart Citations